Age and aging in organized crime in Israel - Amir, Menachim (Crime, law and social change, 2011)
The paper explores the relevance of age and aging in the functioning of organized crime groups in Israel, with a focus on group leaders. Age is connected to two social variables, family and ethnicity. Discussed is the role of age in two clusters: 1) Jewish organized crime groups from Europe, the former Soviet Union and Muslim-majority cultured countries and 2) Israeli Muslim Arab organized crime groups. What part age and aging play in both groups is discussed.